Behaviour of underpinning piles due to shield tunnel installation. Issue 4 (27th June 2019) - Wang, Bolin; Wang, Xu; Ma, Wenjie
Abstract : A laboratory simulation of the number 1 metro line in Lanzhou City, China, was carried out to determine the feasibility of passing through existing bridge projects. The results show that the foundation settlement of the underpinning piles is less than that of the existing piles. A great change in the axial forces on underpinning piles occurs about 10 cm lower than it does on the existing piles. The side friction of the underpinning piles reaches its peak value within the range 20–30 cm. The maximum side friction of an underpinning pile is higher than that of the existing piles. The bearing capacity of the underpinning pile system is larger than that of the existing pile system. In the excavation simulation of a shield tunnel, the axial forces on underpinning piles change in a similar manner as that of the existing piles at excavation depths of 0–20 and 100–120 cm. Negative friction occurs when the depth of excavation is 30 cm, and it reaches a maximum at 20 cm from the tops of the underpinning piles. The neutral point is about 32 cm from the top of the pile body. The load-sharing ratio of the pile cap increases with increases in loading.